2003
DOI: 10.1148/rg.231025054
|View full text |Cite
|
Sign up to set email alerts
|

Major Complications after Radio-frequency Thermal Ablation of Hepatic Tumors: Spectrum of Imaging Findings

Abstract: Although radio-frequency (RF) ablation has been accepted as a promising and safe technique for treatment of unresectable hepatic tumors, investigation of its complications has been limited. According to the multicenter (1,139 patients in 11 institutions) survey data of the Korean Study Group of Radiofrequency Ablation, a spectrum of complications occurred after RF ablation of hepatic tumors. The prevalence of major complications was 2.43%. The most common complications were hepatic abscess (0.66%), peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
291
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(322 citation statements)
references
References 33 publications
8
291
2
3
Order By: Relevance
“…36 While there was no difference in early complication rates according to tumor location, the overall early complication rate of 4.2% in this study may be slightly higher than those reported in other studies. 21,37 The effort of thorough ablation increased the total number of electrode insertions, and this may have led to an increase in complications. Nevertheless, we believe that this will be well compensated by the improved prognosis resulting from complete ablation.…”
Section: Discussionmentioning
confidence: 99%
“…36 While there was no difference in early complication rates according to tumor location, the overall early complication rate of 4.2% in this study may be slightly higher than those reported in other studies. 21,37 The effort of thorough ablation increased the total number of electrode insertions, and this may have led to an increase in complications. Nevertheless, we believe that this will be well compensated by the improved prognosis resulting from complete ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal infection is also a common complication encountered [12,20] . This group of complications consists of hepatic abscess, wound infection and sepsis.…”
Section: Infectionmentioning
confidence: 99%
“…CT scan confirms the diagnosis; air bubbles are usually seen in the abscess. Thus, they may be seen in the ablated area after the procedure and this must not be misdiagnosed as an abscess [20] . Antibiotic prophylaxis is controversial in all patients, but in high risk cases it is recommended [6,12,22,23] .…”
Section: Infectionmentioning
confidence: 99%
“…Careful selection of appropriate patients and RF ablation tools, as well as utilization of adjunctive maneuvers are important to prevent complications. In order to decrease the risk of postprocedural bleeding and tumor seeding, exophytic tumors should be avoided, and a transhepatic route rather than a direct route should be selected to approach peripheral tumors (20). Also, the puncture site should be selected as anteriorly and inferiorly as possible, to prevent a pneumothorax because the pleural space extends more inferiorly in the posterior chest.…”
Section: Rf Ablation In Liver Tumorsmentioning
confidence: 99%
“…Patients with biliary dilatations have an increased risk of developing a postprocedural abscess or sepsis because of bacterial colonization in the biliary tract. Prophylactic use of antibiotics may be beneficial for these patients who are at higher risk for developing infection (20).…”
Section: Rf Ablation In Liver Tumorsmentioning
confidence: 99%